Giada De Laurentiis's recipe for adventure : Miami! - De Laurentiis, Giada; Dougherty, Brandi (De Laurentiis, Giada. Giada De Laurentiis's recipe for adventure., 2015)
When Zia Donatella's latest secret ingredient sends Alfie and Emilia to Miami, Florida, the siblings cook up an adventure full of beautiful beaches, salsa dancing, and deliciously spicy Caribbean food.